Genetic relationship between fenitized ores and hosting dolomite carbonatite of the Bayan Obo REE deposit, Inner Mongolia, China. (1st May 2019) - Wang, Kaiyi; Fang, Aimin; Zhang, Jien; Yu, Liangjun; Dong, Ce; Zan, Jingfeng; Hao, Meizhen; Hu, Fuyou
Graphical abstract: Highlights: Ore-hosting dolomites from the Bayan Obo REE deposit, China, are mostly porphyritic in texture. REE ores are hosted in hypabyssal carbonatite intrusions. Fractionation of carbonatite magmas may have produced evolved melts rich in alkali, REE, Fe and volatile components, which facilitated the formation of REE ore. Abstract: The Bayan Obo deposit is the largest rare-earth element (REE) deposit in the world. In this deposit, ore bodies are hosted in fine-grained ore-bearing dolomite marbles, known as the H8 dolomite marble. The H8 dolomite marble has been considered as part of the Bayan Obo Group composed Paleoproterozoic sedimentary rocks. However, the H8 dolomite marble can be younger than the Bayan Obo Group, and thus, the genesis of the dolomite marble should be re-examined. In this paper, we describe petrography and compositions of the H8 dolomite marble. The dolomite marbles generally have high FeO, MnO and SrO contents, different from sedimentary limestone or dolostone but similar to dolomite carbonatites. In composition, they can be grouped into magnesio-carbonatite and ferro-carbonatite. Texturally they are porphyritic and comprise originally hypabyssal intrusions. It is thus proposed that carbonatitic magmas injected slowly into a magma chamber where they have undergone fractionation to produce evolved dolomite-carbonatite magmas rich in alkali, REE, Fe and volatile components. Such evolved, metal-rich magmas were consequently injected along the contact zone between the early dolomite carbonatite sill and other layer of the Bayan Obo Group, and produced an large fenitization aureole enclosing ores rich in Fe, Nb, REE, F and alkali metals. Changes in CO2 /H2 O ratios, oxygen fugacity and halogen content of fluids were responsible for the formation of different types of ore, including massive magnetite-rich, aegirine-rich and Na-amphibole-rich ores. Considering the fact that the ore bodies are located at the place where dolomite carbonatites are relatively thick and the fenitization is relatively extensive, we speculate that the ore formation was genetically related to extensive fenitization involving exsolution of large amounts of fluids and subsequently extensive metasomatism. It is concluded that carbonatitic magmas played a major role in the formation of the REE mineralization in the Bayan Obo deposit.